THEORETICAL BACKGROUND OF TEACHING SPEAKING IN ENGLISH (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2026)
The article examines the key linguistic, psychological, and pedagogical theories that form the foundation of effective speaking instruction in English language teaching. It focuses on the concept of speaking as a complex communicative skill that involves fluency, accuracy, pronunciation, and pragmatic competence. The article discusses major theoretical approaches such as communicative language teaching, task-based learning, and sociocultural theory, emphasizing their role in creating meaningful interaction and learner-centered instruction. Special attention is given to the importance of interaction, feedback, and learner motivation in developing oral proficiency. The study also analyzes common challenges in teaching speaking, including anxiety, limited exposure to authentic language, and insufficient classroom practice. By synthesizing theoretical perspectives and methodological principles, the article provides a clear framework for understanding how speaking skills can be effectively taught and developed in English language classrooms.